A survey on mathematical proofs among teachers - Chao, ZHOU; Jiansheng, BAO (Frontiers of education in China, 2009)
Mathematical proofs are not only the focus of every country’s mathematics curriculum reforms, but also the subject of research on mathematics education. This paper is based on a survey of mathematics teachers, the goal of which was to investigate the understanding of mathematical proofs of secondary school math teachers, their levels of mathematical proofs, and their ability to comprehensively teach mathematical proofs. Preliminary results of the survey provide insight into several characteristic aspects of Chinese secondary school teachers’ literacy of mathematical proofs.